A comparison of the physicochemical properties of chestnut and highland honey: The case of Senoz Valley in the Rize province of Turkey. (30th May 2021) - Demir Kanbur, Esra; Yuksek, Turan; Atamov, Vagif; Ozcelik, Ali Erdem
Graphical abstract: Highlights: The highest value in colour (L, a, and b) were determined in chestnut honey. The highest value in pH, electrical conductivity, Pb, and Mn were determined in chestnut honey. A total of 146 aromatic components were determined in chestnut and highland honey. (Z)-Hex-3-enyl butyrate, Pentadecanolide and pentylallyl butyrate were found first-time. Abstract: The aim of this study was to determine the physicochemical parameter changes, aroma, melissopalynological properties, and heavy metal content of honey produced from different types of flora (chestnut and highland) in the Senoz Valley. For this purpose, the distribution of beehives at different elevation levels in the research area was determined by a layered random sampling method. Some characteristics of the honey samples were analyzed by standard laboratory methods. The highest average color (L and b) and the glucose, sucrose, Brix, Cd, Pb, Ni, Zn, and Cr values were found in the highland honeys; the highest color (a) and fructose, F/G ratio, proline, pH, conductivity, Fe, Cu, Al, and Mn values were found in the chestnut honeys. The difference between highland and chestnut honeys was statistically significant in terms of color (L and a), F/G ratio, proline, pH, electrical conductivity, Pb, Cu, and Mn. A total of 146 aromatic components were isolated in the chestnut and highland honeys.